Are Labor Supply Decisions Consistent with Neoclassical Preferences? Evidence from Indian Boat Owners - Xavier Gine; Monica Martinez-Bravo; Marian Vidal-Fernández (Institute for the Study of Labor (IZA), 2016)
This paper studies the labor supply of South Indian boat owners using daily labor participation decisions of 249 boat owners during seven years. We test the standard neoclassical model of labor supply and find that boat owners' labor participation depends positively on expected earnings but also on recent accumulated earnings, albeit weakly. Participation elasticities with respect to expected earnings range between 0.8 and 1.3 and about -0.05 and -0.01 with respect to changes in recent income. While the standard neoclassical model is statistically rejected, it is a good approximation of the labor supply behavior of boat owners in southern India.
Keywords: J22; J31; 330; intertemporal labor supply; daily income